2006
DOI: 10.1021/ci050407t
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Bias of Scoring Functions in Structure-Based Virtual Screening

Abstract: A total of 945 known actives and roughly 10 000 decoy compounds were docked to eight different targets, and the resulting poses were scored using 10 different scoring functions. Three different score postprocessing methods were evaluated with respect to improvement of the enrichment in virtual screening. The three procedures were (i) multiple active site correction (MASC) as has been proposed by Vigers and Rizzi, (ii) a variation of MASC where corrections terms are predicted from simple molecular descriptors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Therefore, we focused only on the cocrystallized ligand–protein complexes whose binding conformations were accurately predicted. The C4.5 decision tree (DT) algorithm was used to classify the successful and unsuccessful cases based on 55 physicochemical and structural descriptors of the bait ligand (46 descriptors50–53) and its co‐crystallized proteins (9 descriptors50–53), (Supporting Information Table SV). The number of reverse docking cases was small.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we focused only on the cocrystallized ligand–protein complexes whose binding conformations were accurately predicted. The C4.5 decision tree (DT) algorithm was used to classify the successful and unsuccessful cases based on 55 physicochemical and structural descriptors of the bait ligand (46 descriptors50–53) and its co‐crystallized proteins (9 descriptors50–53), (Supporting Information Table SV). The number of reverse docking cases was small.…”
Section: Resultsmentioning
confidence: 99%
“…This dependency is observed for many scoring functions used in small molecules docking, 73 and different normalization procedures have been proposed in order to allow significant comparison of the binding affinities of different probes in a given pocket. We follow the normalization strategy used by Pan et al, 74 who divided the van der Waals energy by N α , where N is the number of non-hydrogen atoms and α = 1/2 or 1/3; however, in our algorithm α is a free parameter.…”
Section: The Scoring Function and Calculation Of δGmentioning
confidence: 99%
“…It has recently been shown that ligand bias can contribute significantly to the number of false positives in scoring [198]. Some scoring functions favor more complex molecules due to additive descriptors in their underlying mathematical functions, which led to the proposal of different normalization and rescoring approaches [199].…”
Section: Structural Data On Protein-ligand Complexes and Decoy Data Setsmentioning
confidence: 99%